The Educational Relations and Agrarian Life Orientation in the Majapahit Period - Rieca Nona Mutia; Nara Shakti Salsabillah; LR Retno Susanti; Dedi Irwanto (Cetta: Jurnal Ilmu Pendidikan, 2022)
The Majapahit Kingdom is one of the major Hindu-Buddha kingdoms in the Nusantara. The kingdom that has been around for a long time certainly has a lot of history that deserves to be studied, such as the education system, and the system of economic life. Both certainly have an inseparable relationship, between education and the agrarian system of life. The purpose of this study was to determine the relationship between non-formal education and agrarian life in the Majapahit kingdom, both in terms of the economic system and knowledge of the people at that time in their agrarian life, besides that the purpose of this study was to educate readers about informal education. During the Majapahit era and its relationship with the orientation of the agrarian life of the Majapahit kingdom, this discussion is expected to further broaden the reader's insight into the history of the Nusantara. This study uses qualitative methods and historical data collection in order to describe an event, social activity, thought, belief either individually or in groups. As for the results obtained from this study, the Majapahit kingdom was an agrarian kingdom, where the economic sector was in the agricultural sector. The technology used in agriculture has existed since ancient times, but it is still simple. Based on the discussion with this method, we come to a conclusion that, Majapahit was a very developed kingdom in its time, both in terms of education and agrarian life and the relationship between the two was very closely related.